PENGARUH KARAKTERISTIK KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KINERJA TENAGA PENDIDIK DI SEKOLAH MENENGAH PERTAMA NEGERI 19 BATANG HARI - Anggi Rohmawati; Mashudi Hariyanto; Muammar Qadafi (JURNAL ILMIAH NUSANTARA, 2025)
The aim of this research is to analyze the influence of principal characteristics and organizational climate on the performance of teaching staff simultaneously and partially at the 19 Batang Hari State Junior High School. This research uses quantitative methods, used to research certain populations or samples. The population in this sample is all teaching staff at the 19 Batang Hari State Junior High School. The research subjects were 19 teaching staff as respondents. Data collection uses questionnaires and documentation. The statistical hypothesis used to analyze the data in this research is path analysis. The results of this research show that there is a significant influence between the characteristics of the school principal on the performance of the teaching staff, there is a significant influence between the organizational climate on the performance of the teaching staff and there is a significant influence between the characteristics of the school principal and the organizational climate simultaneously on the performance of the teaching staff.